Type of Delivery, Neuropsychological Development and Intelligence in Twin Births - González-Valenzuela, María-José; González-Mesa, Ernesto; Cazorla-Granados, Olga; López-Montiel, Dolores (Frontiers in Psychology, 2019)
Based on a retrospective cohort design with six-year-old children born in twin births, the relationship between verbal, non-verbal, global neuropsychological development, general intelligence and type of delivery has been studied. To this end, the possible effect of third gestational, obstetric and neonatal variables, such as maternal age at delivery, fetal presentation, gestational age, newborn weight and Apgar at minute one, was controlled. The exposed cohort includes children born by cesarean section, and the unexposed cohort is composed of children born vaginally with or without induction. A total of 124 children were evaluated in their first year of primary school using the Child Neuropsychological Maturity Questionnaire, Kaufman's Intelligence Test and the medical histories of the children collected after birth. By means of binary logistic regression analysis, it has been found that the type of delivery is presented as an independent risk factor for disorders in verbal, nonverbal and global development and for the general intellectual difficulties of children born of multiple births. These results suggest the need to analyze in future prospective studies with broader samples the relationship between different types of obstetric and perinatal variables of birth type and infant neuropsychological development and general intelligence, in order to prevent possible psychological alterations from birth.